2022
DOI: 10.2147/imcrj.s384356
|View full text |Cite
|
Sign up to set email alerts
|

Long-Acting Fluocinolone Acetonide Intravitreal Implant for Recurrent Bilateral Non-Infectious Posterior Uveitis

Abstract: Purpose Our case emphasizes the utility of long-acting intravitreal fluocinolone implants (YUTIQ) for managing recalcitrant forms of non-infectious posterior uveitis, NIPU. Patient We present a case of bilateral NIPU refractory to topical corticosteroids and intravitreal triamcinolone and dexamethasone. Results Management with bilateral YUTIQ improved local ocular inflammatory control with improved vision and anatomical outcomes. … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1

Citation Types

0
0
0

Year Published

2024
2024
2024
2024

Publication Types

Select...
2

Relationship

0
2

Authors

Journals

citations
Cited by 2 publications
(2 citation statements)
references
References 10 publications
0
0
0
Order By: Relevance
“…0.18mg Fai (YUTIQ; EyePoint Pharmaceuticals, Watertown, MA, USA) was FDA-approved for the treatment of NIPU in 2018 [27], It has a duration of action of 3 years. Babel et al [28] reported a case of recurrent bilateral NIPU, this patient has a history of localized corticosteroid use and intravitreal injections of TA and DEX, After bilateral injections of 0.18 mg FAi, the patient's BCVA improved from 20/60 to 20/50 in the right eye and from 20/70 to 20/40 in the left eye, and ME and macular leakage were better than before. Similarly, Reddy et al…”
Section: Intravitreal Therapymentioning
confidence: 90%
“…0.18mg Fai (YUTIQ; EyePoint Pharmaceuticals, Watertown, MA, USA) was FDA-approved for the treatment of NIPU in 2018 [27], It has a duration of action of 3 years. Babel et al [28] reported a case of recurrent bilateral NIPU, this patient has a history of localized corticosteroid use and intravitreal injections of TA and DEX, After bilateral injections of 0.18 mg FAi, the patient's BCVA improved from 20/60 to 20/50 in the right eye and from 20/70 to 20/40 in the left eye, and ME and macular leakage were better than before. Similarly, Reddy et al…”
Section: Intravitreal Therapymentioning
confidence: 90%
“…Current evidence suggests that the 0.2 µg/day FAc implant is effective in reducing the need for subsequent treatment with systemic medication [14,15,19,24,25,58,68,71,72].…”
Section: Systemic Therapiesmentioning
confidence: 99%